A case of a novel CACNA1G mutation from a Chinese family with SCA42: A case report and literature review. Issue 36 (September 2018) - Li, Xinyuan; Zhou, Chunkui; Cui, Li; Zhu, Lijun; Du, Heqian; Liu, Jing; Wang, Chenglin; Fang, Shaokuan
Abstract: Rationale: Spinocerebellar ataxia (SCA), a genetically inherited heterogeneous disorder, is characterized by gait ataxia, dysarthria, parkinsonism, choreic movements, dystonia, epilepsy, cognitive and psychiatric symptoms. Spinocerebellar ataxia-42 (SCA42), caused by heterozygous mutation in the calcium channel 1G ( CACNA1G ) gene, is a rare SCA subtype and the transmission pattern is autosomal dominant inheritance. Patient concerns: We presented a novel mutation (c.4721T>A; p.Met1574Lys) in 3 patients from a Chinese family using whole-exome sequencing. All patients exhibited cerebellar ataxia and the clinical manifestations were similar to those that were previously reported in the French and Japanese families. In addition, cerebral magnetic resonance imaging (MRI) showed cerebellar atrophy, and the hot cross bun sign of brainstem was found in the proband and her sister. Diagnoses: The clinical features and MRI findings indicated the diagnosis of SCA. Taken together, the symptoms, MRI findings, as well as whole-exome sequencing made the diagnosis of SCA42 most likely candidate. Interventions and outcomes: The patient was treated with cobamamide (1.5 mg once daily) for nerve nutrition and further physical therapy. At the 4-month follow-up visit, the patient's condition did not improve obviously. Lessons: Recently, a missense mutation in CACNA1G gene (c.5144G4A; p.Arg1715His) was identified in French and Japanese families with SCA42. However, there has been no report of SCA42 or its mutant loci in Chinese patients. Our finding showed a novel mutation in CACNA1G gene and provided important insights into the pathogenesis of SCA42.